2016
DOI: 10.1097/inf.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome of Childhood Bacterial Meningitis With a Single Measurement of C-Reactive Protein

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Peng et al [ 9 ] found that unequal pupils and CSF glucose < 1.5 mmol/L are high risk factors for poor prognosis of refractory bacterial meningitis, but there is a lack of further analysis of factors associated with pathogenic positive bacterial meningitis. Based on our previous research and clinical experience, we selected 23 factors related to refractory outcome or poor prognosis for statistical analysis [ 30 – 32 ] and found that early-stage consciousness disorder, CRP ≥ 50 mg/L, and the isolate bacteria being G + bacteria were independent risk factors for pathogenic positive bacterial meningitis cases to progress to refractory outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al [ 9 ] found that unequal pupils and CSF glucose < 1.5 mmol/L are high risk factors for poor prognosis of refractory bacterial meningitis, but there is a lack of further analysis of factors associated with pathogenic positive bacterial meningitis. Based on our previous research and clinical experience, we selected 23 factors related to refractory outcome or poor prognosis for statistical analysis [ 30 – 32 ] and found that early-stage consciousness disorder, CRP ≥ 50 mg/L, and the isolate bacteria being G + bacteria were independent risk factors for pathogenic positive bacterial meningitis cases to progress to refractory outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the CRP value reflects the severity of the infection [ 30 ]. Similarly, the CRP value can also help predict the prognosis and outcome [ 6 , 25 , 32 ]. Liu Yuming et al [ 34 ] believed that CRP > 100 mg/L is indicative of a poor prognosis for children with pneumococcal meningitis.…”
Section: Discussionmentioning
confidence: 99%